Analysis of HTLV‐1 proviral load (PVL) and antibody detected with various kinds of tests in Japanese blood donors to understand the relationship between PVL and antibody level and to gain insights toward better antibody testing. Issue 8 (14th March 2017) - Matsumoto, Chieko; Sagara, Yasuko; Sobata, Rieko; Inoue, Yukiko; Morita, Maiko; Uchida, Shigeharu; Kiyokawa, Hiroyuki; Satake, Masahiro; Tadokoro, Kenji
Abstract : Adult T‐cell leukemia/lymphoma (ATL) occurs in approximately 5% of individuals infected with human T‐cell leukemia virus type 1 (HTLV‐1). A high proviral load (PVL; more than four copies per 100 peripheral blood mononuclear cells (PBMCs) or 1.6 copies per 100 blood leukocytes) and being male are risk factors for ATL development. Whether anti‐HTLV‐1 antibody level is related to such risk is unknown. Here, PVL and antibody levels were examined using real‐time PCR and other tests in 600 HTLV‐1 positive screened Japanese blood donors to understand the relationship between PVL and antibody level in asymptomatic carriers and to gain insights toward better antibody testing for HTLV‐1 infection. The 430 donors in whom proviral DNA was detected were considered as true positives for HTLV‐1 infection. Among donors aged 40 years or older, more males than females had a PVL corresponding to more than 1.6% infected leukocytes, and an antibody titer below the median ( P = 0.0018). In antibody tests using an HTLV‐1 positive cell line or Env antigens there was a large discrepancy in antibody titer among 13 provirus‐positive samples, probably suggesting that antibody‐based screening tests should incorporate multiple HTLV‐1 antigens, such as Gag and Env antigens.